MENGUNGKAP REALITAS DENGAN PROYEK SENI SEBAGAI METODE PENCIPTAAN KARYA DALAM MEA - Octalyna Puspa Wardany (Graduate School of the Indonesia Institute of the Arts Yogyakarta, 2016)
The implementation acceleration of ASEAN Economic Community from 2020 to be 2015 is not only impacted on economic and politic. It also brings the impact on the freedom of cultural flow. This situation then need the method and tool to creating arts which enable the artists and the actors in arts to works in other countries or places within ASEAN scope which material is the community reality as fusion form between social and cultural (in this term is arts) and also possible with other fields. Through this paper, the researcher would like to propose a method of creating artworks that is the art project which reveals the reality in community as an effort to contribute in advance and develop Indonesia arts world and unearth the arts in terms of ideas of working, creating process, and artworks. This research method is case study of Tentang Hutan Art Project of gerimisUngu Production by reference review, field research and empirical experience, observation, and interview. Based on this case, it found that (1) The Art Project is a method of creating artworks which based on currently reality in the community that is already examined using scientific research; (2) The Art Project is able to be implemented at any location, including MEA context and for any type of arts; (3) The Art Project is enable arts including their artworks become unity with the live; (4) The Art Project does not abandon the aesthetic values as the content of the artworks.